2019
DOI: 10.2147/dmso.s233683
|View full text |Cite
|
Sign up to set email alerts
|

<p>Vitamin B<sub>12</sub> Deficiency and Foot Ulcers in Type 2 Diabetes Mellitus: A Case–Control Study</p>

Abstract: ObjectiveTo assess the association between vitamin B12 deficiency and the development of diabetic foot ulcers (DFU) in type 2 diabetes mellitus (T2DM).MethodsThis is a case–control study that enrolled 323 Saudi adults with T2DM randomly selected from the Jazan Diabetes & Endocrine Center, Saudi Arabia from January 1, 2019, to July 31, 2019. The sample included 108 newly diagnosed cases with DFU and 215 control participants with T2DM unaffected by and free of foot ulcers (1:2 ratio). Logistic regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Jazan Region is situated in southwestern Saudi Arabia and is characterized by a relatively homogenous population with similar ethnic and socioeconomic characteristics. [10][11][12] In the current study, a diagnosis of COVID-19 was confirmed by the identification of viral RNA in a nasopharyngeal swab sample using real-time reverse transcription-polymerase chain reaction (LightCycler ® 480 Instrument II, Roche).…”
Section: Methodsmentioning
confidence: 68%
“…Jazan Region is situated in southwestern Saudi Arabia and is characterized by a relatively homogenous population with similar ethnic and socioeconomic characteristics. [10][11][12] In the current study, a diagnosis of COVID-19 was confirmed by the identification of viral RNA in a nasopharyngeal swab sample using real-time reverse transcription-polymerase chain reaction (LightCycler ® 480 Instrument II, Roche).…”
Section: Methodsmentioning
confidence: 68%
“…Similar results were found in previous studies conducted in Jazan. [30][31][32] It has been found that DM-related distress 18,19,22 and depression 18,22 have a negative impact on glycemic control. In psychological conditions such as DM distress and depression, regulatory hormones and neurotransmitters, such as catecholamine, glucocorticoids, growth hormones, and glucagon, are activated.…”
Section: Discussionmentioning
confidence: 99%
“…This case–control study was conducted on Saudi patients with COVID-19 in Jazan Region, located in southwestern Saudi Arabia and characterized by a relatively homogenous population with similar ethnic and socioeconomic characteristics [ [10] , [11] , [12] , [13] , [14] ].…”
Section: Methodsmentioning
confidence: 99%